Perceived quality of primary healthcare services among the National Health Insurance members and fee for service patients in the West Denpasar II Public Health Center Bali, Indonesia - Nitya Nijyoti; Putu Ayu Indrayathi; I Made Ady Wirawan (Public Health and Preventive Medicine Archive, 2020)
Background and purpose: The Government of Indonesia established the National Health Insurance or in Indonesia called Jaminan Kesehatan Nasional (JKN) in 2014 with the target of achieving universal health coverage (UHC) by 2019. However, many have not become JKN participants and still use the fee for service financing system. The purpose of this study was to determine patient’s perceptions of the quality of health services under the JKN and fee for service payment methods. Methods: A cross-sectional study was conducted at West Denpasar II Public Health Centre (PHC) with 133 outpatient respondents who were selected sequentially. Data collection was carried out in June 2019 through interviews. Patients’ perceptions of service quality were measured according to the six domains of health service quality established by the Institute of Medicine (IOM) which include effectiveness, efficiency, timeliness, patient-centered approach, safety and equity. Bivariate analysis was conducted with Mann Whitney test and multivariate analysis with Ancova. Results: Patients’ perceptions of the quality of services in the JKN and fee for service payment methods were found to be quite good with an average of 3.08 and 3.17 of the maximum value of 4.0. Bivariate analysis showed a significant difference with a mean rank of 54.28 for JKN and 79.16 for fee for service (p<0.01). Patients’ perceptions of service quality also differed significantly based on the dimensions of efficiency (p=0.001), effectiveness (p=0.005), timeliness (p=0.007) and patient-centered approach (p=0.032). Multivariate analysis showed that the variable that was significantly related to patient perceptions of service quality was the payment methods (p<0.001). Conclusion: Patients with a fee for service payment methods have a better perception of service quality than patients who use JKN. Advocacy to policy makers and service providers should be conducted in order to ensure the equal quality of service for all patients.